Sequence comparison of `states' of a1-m1 suggests a model of Spm (En) action - Schwarz-Sommer, Zsuzsanna (1985)
Two states of the a1-m1 allele featuring different phenotypes in the absence as well as in the presence of Spm or En have been cloned and sequenced. The insertion site and orientation of the Inhibitor (I) element within the two alleles is identical. The sizes of the I elements differ, being 2.2 kb in state 6078 and 789 bp in state 5719A-1. The internal deletion in state 5719A-1 affects sequences within one side of the terminal inverted repeats of the I element. This alteration can be correlated with the decreased response of this state to the Mutator function of Spm. A model for the interaction between Spm (En)-encoded functions and the receptor element is discussed explaining the phenotypic differences between the states of the locus.